2010
DOI: 10.1080/02607476.2010.513863
|View full text |Cite
|
Sign up to set email alerts
|

Educational collaboration across borders: the preparation of the Transforming teacher education. Redefined professionals for 21st century schools report

Abstract: This paper provides an account of the processes leading to the report Transforming teacher education. Redefined professionals for 21 st century schools undertaken by the International Alliance of Leading Education Institutes. The report is a unique document, neither a series of country studies nor one based on an extensive review of the literature. Rather, it attempted to strongly reflect widely varying contexts and responses in teacher education in Asia, Europe, Brazil, Canada and the USA given key global imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…International collaboration proved to be a source of inspiration and learning for the participants (Tan et al, 2010;Whatley & Bell, 2003) and the students gained a chance to assimilate new knowledge from other parts of the world. A variety of perspectives were made available to these students who otherwise would not have had a chance to familiarize themselves with such views.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…International collaboration proved to be a source of inspiration and learning for the participants (Tan et al, 2010;Whatley & Bell, 2003) and the students gained a chance to assimilate new knowledge from other parts of the world. A variety of perspectives were made available to these students who otherwise would not have had a chance to familiarize themselves with such views.…”
Section: Discussionmentioning
confidence: 99%
“…This provides students a space to share their ideas and experiences in a non-threatening setting. Owing to the changing teaching and learning scenario, it is important to introduce collaborative teaching methodologies in the classrooms (Tan, Wong, Fang, & Gopinathan, 2010). Collaborative groups encourage individual participation, taking responsibility, sharing and encouraging to highlight individual abilities and contribution.…”
Section: Collaborative Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way the cross-cultural research reported in her paper extends work also published in JET, so adding to the wide variety of social contexts that are represented in JET's comparative approach to teacher education, which include, amongst many others, Indonesia (Udin and Johnston 2006), Japan (Suzuki 2008), Singapore (Tan et al 2010), South Korea (Seongja 2008), and Turkey (Seferoğlu, 2006). Erika Hepple, based in a different Australian university, also presents a collaborative project involving pre-service student teachers from Hong Kong on a studyabroad programme in Australia.…”
mentioning
confidence: 85%
“…In 2008, the International Alliance of Leading Education Institutes (IA) produced a report on transforming teacher education based on data from Asia, Europe, Brazil, Canada and the USA. The key drivers were identified as the rapid rate of economic integration, technological advances, global competition for talent, continued underachievement (particularly among minorities and marginalised populations), diverse classrooms, and increased expectations from stakeholders (Tan, Wong, Fang, Devi & Gopinathan 2010).…”
Section: Introductionmentioning
confidence: 99%